EDUCATIONAL INFLUENCE OF ADVERTISING (Pedagogy of Higher and Secondary Education, 2022)
In this article is studied the question about the influence of advertising in education of growing young generation. On the basis of concrete examples of advertising products, the author analyzes their influence on education of youth.
Keywords: 1